Quwat-e-Iqtadar - Russell, Bertrand; Translated by Raiz Mehmood Anjam (Lahore FIction House, 2017)
"The key to human nature that Marx found in wealth and Freud in sex, Bertrand Russell finds in power. Power, he argues, is man's ultimate goal, and is in its many guises the single most important element in the development of any society."
Keywords: Political science -- Executive power -- Power (Social sciences)